Third-Year Pharmacy Students' Work Experience and Attitudes and Perceptions of the Pharmacy Profession - Siracuse, Mark V. (American Journal of Pharmaceutical Education, 2008)
OBJECTIVES: To describe PharmD students' work experiences and activities; examine their attitudes towards their work; examine perceptions of preceptor pharmacists they worked with; and determine important issues associated with career preference. METHODS: A written survey was administered to third-year doctor of pharmacy (PharmD) students at 8 colleges and schools of pharmacy in the Midwest. RESULTS: Five hundred thirty-three students (response rate = 70.4%) completed the survey instrument. Nearly 100% of PharmD students reported working in a pharmacy by the time their advanced pharmacy practice experiences (APPEs) began. Seventy-eight percent reported working in a community pharmacy, and 67% had worked in a chain community pharmacy. For all practice settings, students reported spending 69% of their time on activities such as compounding, dispensing, and distribution of drug products. CONCLUSIONS: Most students are working in community pharmacy (mainly chain) positions where their primary function is traditional drug product dispensing and distribution. Having a controllable work schedule was the variable most strongly associated with career choice for all students.